Brain–computer interface treatment for gait rehabilitation in stroke patients - Sebastián-Romagosa, Marc; Cho, Woosang; Ortner, Rupert; Sieghartsleitner, Sebastian; Von Oertzen, Tim J.; Kamada, Kyousuke; Laureys, Steven; Allison, Brendan Z.; Guger, Christoph (Frontiers in Neuroscience, 2023)
The use of Brain–Computer Interfaces (BCI) as rehabilitation tools for chronically ill neurological patients has become more widespread. BCIs combined with other techniques allow the user to restore neurological function by inducing neuroplasticity through real-time detection of motor-imagery (MI) as patients perform therapy tasks. Twenty-five stroke patients with gait disability were recruited for this study. Participants performed 25 sessions with the MI-BCI and assessment visits to track functional changes during the therapy. The results of this study demonstrated a clinically significant increase in walking speed of 0.19 m/s, 95%CI [0.13–0.25], p < 0.001. Patients also reduced spasticity and improved their range of motion and muscle contraction. The BCI treatment was effective in promoting long-lasting functional improvements in the gait speed of chronic stroke survivors. Patients have more movements in the lower limb; therefore, they can walk better and safer. This functional improvement can be explained by improved neuroplasticity in the central nervous system.